#TITLE_ALTERNATIVE# - T. R. GINTING (NIM 25098033), DJAYANTA
Government of Indonesia, through the Directorate General of Highways, has established a bridge treatment system known as Bridge Management System (BMS). One of the activities of this system is planning and programming, which functioned to ensure the optimality of bridge maintenance cost allocation. It is done by technical screening and economic evaluation to assign the priority treatment (development, replacement, rehabilitation, and routine maintenance) of a bridge.In the context of planning and programming, BMS have not measured the efficiency of bridge maintenance. Maintenance efficiency is defined as a measure of how well maintenance cost allocation improves a bridge performance.Therefore, BMS doesn't know how maintenance cost allocation influences the improvement of bridge performance beyond its service life, relative to the other bridges. The optimality of bridge maintenance cost allocation based on technical screening and economic evaluation, doesn't really ensure the efficiency of bridge maintenance relative to the other bridges maintenance cost allocation. This research discusses the relative efficiency of bridge maintenance in BMS and assigns the best pattern of bridge maintenance cost allocation using Data Envelopment Ana/ysis/DEA method. The word relative means that the measurement of bridge maintenance efficiency is compared with the other bridges maintenance. This caused of BMS didn't have a standard of bridge maintenance. The maintenance parameters considered are rehabilitation expenditure, routine maintenance expenditure, annually average daily traffic, condition mark, on going service life, and width of bridge. The best pattern of maintenance cost allocation is provided by the efficient bridge maintenance. The pattern of maintenance cost allocation provided by this research can improve or enhance the function of BMS. As result, bridge maintenance could be optimum and efficient.